2009
DOI: 10.1371/journal.pone.0005668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Growth Hormone (GH) Deficiency and GH Replacement upon Thymus Function in Adult Patients

Abstract: BackgroundDespite age-related adipose involution, T cell generation in the thymus (thymopoiesis) is maintained beyond puberty in adults. In rodents, growth hormone (GH), insulin-like growth factor-1 (IGF-1), and GH secretagogues reverse age-related changes in thymus cytoarchitecture and increase thymopoiesis. GH administration also enhances thymic mass and function in HIV-infected patients. Until now, thymic function has not been investigated in adult GH deficiency (AGHD). The objective of this clinical study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 38 publications
3
53
0
2
Order By: Relevance
“…Contrary to popular opinion, the thymus continues to function throughout life and plays a fundamental role in the recovery of a competent T-cell repertoire after intensive chemotherapy or during highly active antiretroviral chemotherapy in human immunodeficiency virus infection [60,61]. The integrity of the somatotrope growth hormone/IGF-1 axis is known to be important for the maintenance of thymus function in adult life [62 ].…”
Section: Environmental Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Contrary to popular opinion, the thymus continues to function throughout life and plays a fundamental role in the recovery of a competent T-cell repertoire after intensive chemotherapy or during highly active antiretroviral chemotherapy in human immunodeficiency virus infection [60,61]. The integrity of the somatotrope growth hormone/IGF-1 axis is known to be important for the maintenance of thymus function in adult life [62 ].…”
Section: Environmental Factorsmentioning
confidence: 95%
“…Contrary to popular opinion, the thymus continues to function throughout life and plays a fundamental role in the recovery of a competent T-cell repertoire after intensive chemotherapy or during highly active antiretroviral chemotherapy in human immunodeficiency virus infection [60,61]. The integrity of the somatotrope growth hormone/IGF-1 axis is known to be important for the maintenance of thymus function in adult life [62 ].The thymus constitutes the central arm of immunological self-tolerance by two essential mechanisms that are intimately associated with, and paradoxically mediated by, the same thymic self-antigens: first, clonal deletion of self-reactive T cells issued from the random recombination of TCR genes (negative selection) and second, generation of self-antigen-specific natural regulatory T cells (nTregs) that are able to inactivate in periphery selfreactive T cells having escaped intrathymic negative selection [63 ,64].For a long time, peripheral tissue-restricted antigens targeted by autoimmune processes were thought to be sequestered from T cells during their intrathymic differentiation. We and several other groups have demonstrated that thymic epithelial cells (TECs) from different species constitute a site for the promiscuous transcription of a great number of genes encoding tissuerestricted antigens or belonging to neuroendocrine families, such as the neurohypophysial family, tachykinins, neurotensins, somatostatins, atrial natriuretic peptides, and the insulin family.…”
mentioning
confidence: 94%
“…Furthermore, these increases of TREC frequency and T-cell gain are correlated to an increase of plasma IGF-1 [15], arguing for a crucial role of IGF-1 in GH-mediated stimulation of thymic T-cell production. Investigation of thymopoiesis in adult GH deficiency (AGHD) has demonstrated that, after GH withdrawal, intrathymic T-cell proliferation and thymic T-cell output decreased whereas resumption of GH treatment led to an increase of thymopoiesis to a level close to the one before withdrawal of GH treatment [16]. Again, in this study, the close correlation between plasma IGF-1 concentrations and the frequency of sjTREC in PBMC suggests that the thymotropic properties of GH could be mediated by IGF-1 [16].…”
Section: Effects On Thymocyte Numbermentioning
confidence: 99%
“…Investigation of thymopoiesis in adult GH deficiency (AGHD) has demonstrated that, after GH withdrawal, intrathymic T-cell proliferation and thymic T-cell output decreased whereas resumption of GH treatment led to an increase of thymopoiesis to a level close to the one before withdrawal of GH treatment [16]. Again, in this study, the close correlation between plasma IGF-1 concentrations and the frequency of sjTREC in PBMC suggests that the thymotropic properties of GH could be mediated by IGF-1 [16]. It should be also noted that the effects of the somatotrope GH/IGF-1 axis on thymocytes might be relayed by other soluble factors like cytokines.…”
Section: Effects On Thymocyte Numbermentioning
confidence: 99%
See 1 more Smart Citation